Pelatihan Literasi Digital untuk Guru dan Siswa dalam Meningkatkan Kualitas Pembelajaran Jarak Jauh - Windarto, Agus Perdana; Hutahaean, Jeperson; Sussolaikah, Kelik; Setiawansyah, Setiawansyah (Jurnal Pengabdian Masyarakat Inovasi, 2026)
This community service activity aims to improve the digital literacy of teachers and students to support the quality of distance learning. The implementation method was carried out through practice-based training involving 20 participants from among teachers and students. Evaluation results showed that before the activity, the digital literacy level of participants was in the basic to intermediate category with an average score of 1-2, while after the activity there was a significant increase to an average score of 4-5. Participants' satisfaction responses also showed that 80% expressed satisfaction or were very satisfied, confirming the effectiveness of the training. This activity successfully addressed the needs of partners regarding the constraints of low digital competency in online learning, despite the limitations of the limited number of participants and the short duration of implementation. Therefore, this activity is recommended to be expanded and integrated into the ongoing professional development program for teachers and students.